Identification of Locations for Potential Glacial Lakes Formation using Remote Sensing Technology - Yagol, P; Manandhar, A; Ghimire, P; Kayastha, RB; Joshi, JR (Journal on Geoinformatics, Nepal, 2013)
In past Nepal has encountered a number of glacial lake outburst flood (GLOF) events causing loss of billions of rupees. Still there are a number of glacial lakes forming and there are chances of new glacial lake formation. Hence there is intense need to monitor glaciers and glacial lakes. The development on remote sensing technology has eased the researches on glacier and glacial lakes. Identification of locations of potential glacial lakes through the use of remote sensing technology has been proven and hence is opted for identification of locations of potential glacial lake in Khumbu Valley of Sagarmatha Zone, Nepal. The probable sites for glacial lake formation are at Ngojumpa, Lobuche, Khumbu, Bhotekoshi, Inkhu, Kyasar, Lumsumna, etc. As per study, the biggest glacial lake could form at Ngozumpa glacier. Even in other glaciers potential supra-glacial lakes could merge together to form lakes that occupy significant area. Nepalese Journal on Geoinformatics -12, 2070 (2013AD): 10-16